Transforming the probability density function (PDF)

Let us consider the transformation of probability density function under two cases: transformation with a random variable and with a random vector.

Case 1: Random variable


  • A random variable \(z\) with PDF \(\pi(z)\).
  • A transformation \(x=f(z)\).

We have the inverse transformation \(z=f^{-1}(x)\). The target is to get the PDF of \(x\), denoted as \(p(x)\) of the new random variable \(x\).

The CDF of \(z\), \(F_Z(z)\), is \(\mathbb{P}(Z \leq z)\).

The CDF of \(x\), \(F_X(x)\), is \(\mathbb{P}(X \leq x)\).

Using the transformation \(x=f(z)\), we can write the CDF of \(x\) in terms of \(z\):

\[F_X(x) = \mathbb{P}(X \leq x) = \mathbb{P}(f(Z) \leq x) =\mathbb{P}(Z \leq f^{-1}(x)) =F_Z(f^{-1}(x)) .\]

Differentiate \(F_X(x)\) with respect to \(x\) to obtain the PDF \(p(x)\):

\[p(x) = \frac{dF_X(x)}{dx} = \frac{dF_Z(f^{-1}(x))}{dx}\]

Using the chain rule for differentiation:

\[\frac{dF_Z(f^{-1}(x))}{dx} = \frac{dF_Z(f^{-1}(x))}{d(f^{-1}(x))} \cdot \frac{d(f^{-1}(x))}{dx} .\]

The derivative of the CDF \(F_Z(z)\) with respect to \(z\) is the PDF \(\pi(z)\):

\[\frac{dF_Z(z)}{dz} = \pi(z) .\]


\[p(x) = \pi(f^{-1}(x)) \cdot \frac{d(f^{-1}(x))}{dx} .\]

Alternatively, using \(z = f^{-1}(x)\) and the inverse function theorem:

\[\frac{d(f^{-1}(x))}{dx} = \frac{1}{\frac{df(z)}{dz}|_{z=f^{-1}(x)}} .\]


\[p(x) = \pi(f^{-1}(x)) \left| \frac{d}{dx} f^{-1}(x) \right| .\]

Case 2: Random vector


  • A random vector \(\mathbf{z}\) with joint PDF \(\pi(\mathbf{z})\).
  • A transformation \(\mathbf{x} = f(\mathbf{z})\). The inverse transformation can also be written as \(\mathbf{z} = f^{-1}(\mathbf{x})\), and we want to get the joint PDF \(p(\mathbf{x})\) of the new random vector \(\mathbf{x}\).

1. Jacobian Determinant:

The transformation \(\mathbf{x} = f(\mathbf{z})\) involves multiple variables, so we need to consider the Jacobian matrix of partial derivatives:

\[J = \frac{\partial(x_1,x_2,\ldots,x_n)}{\partial(z_1,z_2,\ldots,z_n)} = \begin{pmatrix} \frac{\partial x_1}{\partial z_1} & \frac{\partial x_1}{\partial z_2} & \cdots & \frac{\partial x_1}{\partial z_n} \\ \frac{\partial x_2}{\partial z_1} & \frac{\partial x_2}{\partial z_2} & \cdots & \frac{\partial x_2}{\partial z_n} \\ \vdots & \vdots & \ddots & \vdots \\ \frac{\partial x_n}{\partial z_1} & \frac{\partial x_n}{\partial z_2} & \cdots & \frac{\partial x_n}{\partial z_n} \\ \end{pmatrix} .\]

2. Change of Variables Formula:

The joint PDF \(p(\mathbf{x})\) is given by:

\[p(\mathbf{x}) = \pi(\mathbf{z}) \cdot |\text{det}(J)| \text{ where } \mathbf{z} = f^{-1}(\mathbf{x}).\]

Here, \(|\text{det}(J)|\) is the determinant of the Jacobian matrix.

Special Case: Linear Transformation

If \(\mathbf{z} \sim \mathcal{N}(\mu,\sigma^2)\) and the transformation is linear, such as \(\mathbf{x} = a\mathbf{z} + b\), the resulting distribution will also be normal due to the properties of the normal distribution.

For a linear transformation \(\mathbf{x} = a\mathbf{z} + b\):

\[\mathbf{x} \sim \mathcal{N}(a\mu + b,(a\sigma)^2).\]